Improving early childhood pre-service teachers' computational thinking teaching self-efficacy beliefs in a STEM course - Ciftci, Ayse; Topcu, Mustafa Sami (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
Background In order for computational thinking (CT) to be successfully implemented in educational environments, teachers' CT teaching self-efficacy beliefs should be developed. The existing research on this topic is generally focused on training in-service teachers on CT to develop their self-efficacy. Conversely, the current study aims to contribute to the development of early childhood pre-service teachers' CT teaching self-efficacy beliefs through CT-integrated STEM education. Purpose In the current study, the effect of CT-integrated STEM education on CT teaching self-efficacy beliefs of early childhood pre-service teachers was explored. Sample The study group was composed of 68 second-year early childhood pre-service teachers. All were attending a state university in the city of Istanbul during the 2020-2021 academic year. Design and Methods The study employed a quasi-experimental design, i.e. the control group was given only STEM education, while the experimental group was given CT-integrated STEM education. The data collection tool used in the current study was 'the scale of self-efficacy beliefs towards teaching computational thinking'. For analysis, an independent samples t-test and a paired samples t-test were used. Results The findings have revealed that there is a significant difference in the post-test scores on the 'scale of self-efficacy beliefs towards CT teaching' in favor of the experimental group. The effect size calculated for the difference between the mean pre-test and post-test scores of the experimental group students was found to be large. These results show that CT-integrated STEM education contributed to the development of the pre-service teachers' CT teaching self-efficacy beliefs. Conclusion The current study contributes to the literature by showing that CT-integrated STEM education fosters pre-service teachers' professional development and their self-efficacy beliefs about CT teaching.
Keywords: Computational thinking teaching; computational thinking integrated STEM education; self-efficacy beliefs; STEM education; early childhood pre-service teachers; STUDENTS; Education & Educational Research